Active and latent tuberculosis in prisoners in the Central-West Region of Brazil - Anderson Oliveira Estevan; Sandra Maria do Valle Leone de Oliveira; Julio Croda (Revista da Sociedade Brasileira de Medicina Tropical, 2013)
Introduction Jailed populations exhibit high rates of tuberculosis (TB) infection and active disease. Methods A cross-sectional study was performed to estimate the prevalence of latent and active TB and to identify factors associated with latent infection in inmates. Results The prevalence of latent TB was 49%, and the prevalence of active TB was 0.4%. The presence of a Bacille Calmette-Guérin (BCG) scar (prevalence ratio (PR)=1.65; 95% confidence interval (CI): 1.09-2.50; p=0.0162) and the World Health Organization (WHO) score for active TB in prisons (PR=1.07; 95% CI: 1.01-1.14; p=0.0181) were correlated with infection. Conclusions The identification of associated factors and the prevalence of latent and active TB allows the development of plans to control this disease in jails.